83 RETROSPECTIVE REVIEW OF CHEMOTHERAPY RESPONSE IN LARGE CELL NEUROENDOCRINE CARCINOMA OF THE LUNG. (1st January 2006) - Baker, J.; Khansur, T.; Elkins, S.; Moore, A.
Abstract : Purpose: The objective of our study was to assess chemotherapy treatment with regards to radiographic or clinical response along with survival in patients with large cell neuroendocrine carcinoma of the lung. Methods: Eleven patients were identified, and the type of chemotherapy, best response, and overall survival were assessed in each patient. Results: One patient with stage IB disease underwent surgical lobectomy, relapsed 23.1 months later, and obtained stable disease with paclitaxel and carboplatin with an overall survival of 31.7 months. One with stage IIA disease recurred 57 months following surgical lobectomy and received no response to etoposide and carboplatin with an overall survival of 76 months. Two patients with stage III disease were identified, and one with stage IIIA disease achieved a partial response and overall survival of 7.7 months with etoposide and carboplatin. The other patient with stage IIIB disease experienced stable disease with paclitaxel and carboplatin with an overall survival of 12.8 months. The remaining seven patients had stage IV disease at the time of diagnosis. Four of these patients received etoposide and platinum chemotherapy, with one patient experiencing stable disease and an overall survival of 18 months. One patient had no response to etoposide and platinum, with an overall survival of 0.5 months from the time of diagnosis. The remaining two patients who received etoposide and platinum achieved a partial response and complete response with overall survivals of 10.3 months and 36.4 months, respectively. Three patients wit stage IV disease received paclitaxel and platinum, with one patient experiencing stable disease with an overall survival of 14.1 months. The other two patients who received paclitaxel and platinum achieved no response with overall survivals of 7.2 months and 7.6 months. Conclusions: The response of large cell neuroendocrine carcinoma of the lung to chemotherapy is poor regardless of the treatment strategy when employing classic small cell lung cancer or non-small cell lung cancer regimens. Optimal therapy for early-stage disease in this review was resection, but both cases eventually recurred.